Revitalisasi Nilai-Nilai Islam Moderat Melalui Inovasi Diplomasi Digital di Era 5.0: Studi Kasus Diplomasi Qatar - Muhammad Aminullah; Bashori (Journal of Communication and Da'wah, 2025)
This study examines Qatar’s digital diplomacy strategy in promoting the values of moderate Islam and explores its relevance for diplomatic practices in the era of 5.0. The research focuses on Qatar’s implementation of digital diplomacy, the core values of moderate Islam projected through digital platforms, and how these approaches offer a value-based diplomacy model for an increasingly digitized global environment. This research employs a qualitative method with a library research approach, drawing data from official documents, government digital platforms, international media networks, and academic literature. The findings indicate that Qatar effectively utilizes Al-Jazeera, official government social media channels, and global events such as the 2022 FIFA World Cup to promote values of tolerance, justice, peace, and intercivilizational dialogue. Qatar’s model demonstrates that religious and ethical principles can be integrated into global communication strategies through a structured technological approach. Its relevance to the 5.0 era lies in the potential development of value-based digital diplomacy, which emphasizes ethics, moderation, and social cohesion alongside technological advancement.